Linear programming optimization of local food-based recommendations for undernourished urban poor Malaysian children aged 2 to 5 years - Miow, Yee Xuen; Gan, Wan Ying; Fahmida, Umi; Lim, Poh Ying; Appannah, Geeta (SAGE Publications, 2025)
Background: Poor diet quality may contribute to undernutrition, particularly affecting young children from low-income households. Therefore, affordable and healthy local food-based recommendations (FBRs) are needed. Objectives: This study aimed to (1) identify problem nutrient(s), (2) identify locally available nutrient-dense food sources that can provide adequate nutrients to meet the recommended dietary intakes of undernourished urban poor children aged 2–5 years, and (3) use linear programming to recommend a daily diet based on the current food patterns that achieves dietary adequacy and meets average food costs for these children. Methods: A cross-sectional study was conducted in Seremban, Malaysia. Three-day 24hour dietary recalls were collected from the mothers (n =168). Food costs were estimated using market surveys. The FBRs were formulated by linear programming analysis using Optifood software. Results: Folate was an “absolute problem nutrient” (such a nutrient does not achieve the 100% recommended nutrient intake even upon diet optimization). Full-cream milk, chocolate malted milk, fortified cornflakes, and chicken egg were the common locally available nutrient-dense foods that would provide adequate nutrients to meet the recommended dietary intakes of undernourished urban poor children. The final FBR set would ensure dietary adequacy for eight to nine of 11 nutrients at a cost of ringgit Malaysia (RM) 4.80/day (US $1.05/day) and RM6.20/day (US $1.34/day), depending on the age group. Conclusions: Interventions are required to ensure dietary adequacy for undernourished urban poor children under 5 years old. Dietary adequacy could be improved via realistic changes in habitual food consumption practices.